Color Image Visual Secret Sharing with Expressive Shares using Color to Gray & Back and Cosine Transform - Chaturvedi, Ratnesh Naresh; Thepade, Sudeep D; Ahirrao, Swati (ELCVIA Electronic Letters on Computer Vision and Image Analysis, 2023)
Color Visual Secret Sharing (VSS) is an essential form of VSS. It is so because nowadays, most people like to share visual data as a color image. There are color VSS schemes capable of dealing with halftone color images or color images with selected colors, and some dealing with natural color images, which generate low quality of recovered secret. The proposed scheme deals with a color image in the RGB domain and generates gray shares for color images using color to gray and back through compression. These shares are encrypted into an innocent-looking gray cover image using a Discrete Cosine Transform (DCT) to make meaningful shares. Reconstruct a high-quality color image through the gray shares extracted from an innocent-looking gray cover image. Thus, using lower bandwidth for transmission and less storage.